Cover Feature: Structural Insights into Hysteretic Spin‐Crossover in a Set of Iron(II)‐2, 6‐bis(1H‐Pyrazol‐1‐yl)Pyridine) Complexes (Chem. Eur. J. 6/2022). Issue 6 (22nd January 2022) - Suryadevara, Nithin; Mizuno, Asato; Spieker, Lea; Salamon, Soma; Sleziona, Stephan; Maas, André; Pollmann, Erik; Heinrich, Benoît; Schleberger, Marika; Wende, Heiko; Kuppusamy, Senthil Kumar; Ruben, Mario
Abstract : Bistable spin‐state switching near room temperature : Two mononuclear iron(II) complexes showing technologically relevant abrupt and wide hysteretic, bistable spin‐state switching characteristics in the vicinity of room temperature are reported. The large structural reorganizations from the Jahn–Teller‐distorted high‐spin state to the less distorted low‐spin state and ethyl group conformational switching are proposed as the main contributing factors rendering the switching hysteretic. More information can be found in the Research Article by M. Schleberger, H. Wende, S. K. Kuppusamy, M. Ruben, et al. (DOI: 10.1002/chem.202103853 ).